2011
DOI: 10.1371/journal.pone.0028236
|View full text |Cite
|
Sign up to set email alerts
|

Basic Taste Stimuli Elicit Unique Responses in Facial Skin Blood Flow

Abstract: Facial expression changes characteristically with the emotions induced by basic tastes in humans. We tested the hypothesis that the five basic tastes also elicit unique responses in facial skin blood flow. Facial skin blood flow was measured using laser speckle flowgraphy in 16 healthy subjects before and during the application of basic taste stimuli in the oral cavity for 20 s. The skin blood flow in the eyelid increased in response to sweet and umami taste stimuli, while that in the nose decreased in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 26 publications
4
36
1
Order By: Relevance
“…Infrequent toxic effect is observed (13) . The subjects who drink the tea found it an unpleasant beverage, which agrees with the results that show that bitter taste is unpleasant for humans (8,12) . In the evaluation of the recognition of bolus taste, 94% of the subjects were found to recognize the sweet bolus (sucrose) and 91% recognized the bitter bolus (quinine sulfate) (12) , results similar to our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Infrequent toxic effect is observed (13) . The subjects who drink the tea found it an unpleasant beverage, which agrees with the results that show that bitter taste is unpleasant for humans (8,12) . In the evaluation of the recognition of bolus taste, 94% of the subjects were found to recognize the sweet bolus (sucrose) and 91% recognized the bitter bolus (quinine sulfate) (12) , results similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…Bitter taste cause a decrease in skin blood flow (8) , and a stronger autonomic nervous system response compared with other tastes (12) . These responses do not alter swallowing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many researchers have attempted to achieve emotion recognition using facial expressions 1, 2, 3) , voices 4,5,6) and, in particular, physiological signals 7,8,9,10,11) . Studies on physiological psychology have revealed a strong association between the physiological response of the autonomic nervous system and the human emotional state.…”
Section: Introductionmentioning
confidence: 99%
“…Kashima et al 7) used laser speckle flowgraphy to measure the blood flow in the facial skin of 16 healthy participants before and after experiencing the five tastes, sweet, sour, salty, umami and bitter. Their results showed unique facial skin blood flow patterns for each taste stimuli.…”
Section: Introductionmentioning
confidence: 99%